Urban spatial structure and environmental efficiency: Empirical analysis from prefecture-level cities in China - Ye, Jing; Wei, Feng; Liu, Xihe; Li, Jinkai (Frontiers in Environmental Science, 2022)
China's environmental problems are emerging with the continuous development of the economy and urbanization. The influence of urban spatial structure on the environment has attracted more and more attention from scholars and urban planners. Based on the fusion-corrected DMSP-OLS and NPP-VIIRS nighttime light data, we constructed spatial structure indicators of 276 prefecture-level cities. Moreover, we explored the impact of urban spatial structure on environmental efficiency from the monocentric and polycentric spatial structures. The results show that the monocentric spatial structure has higher environmental efficiency than the polycentric spatial structure. It can improve environmental efficiency through learning, sharing, and matching mechanisms. At the same time, we found that population size and density had a robust moderating effect. When the resident population size of a city is higher than 5 million and the population density is higher than 280 persons/km2, the monocentric spatial structure has a negative impact on environmental efficiency. In contrast, the polycentric spatial structure is more effective in improving environmental efficiency. Finally, through further discussion, we also found that the point-based household registration policy adopted by the government to control population size has no significant impact on environmental efficiency, while the environmental information disclosure policy can effectively improve environmental efficiency. Our findings offer a basis for the Chinese government to formulate urban planning and environmental protection policies and provide experience for other developing countries.